A peptide-gated ion channel from the freshwater polyp Hydra - Golubovic, Andjelko; Kuhn, Anne; Holstein, Thomas W. (The journal of biological chemistry, 2007)
Chemical transmitters are either low molecular weight molecules or neuropeptides. As a general rule, neuropeptides activate only slow metabotropic receptors. To date, only one exception to this rule is known, the FMRFamide-activated Na+ channel (FaNaC) from snails. Until now FaNaC has been regarded as a curiosity, and it was not known whether peptide-gated ionotropic receptors are also present in other animal groups. Nervous systems first evolved in cnidarians, which extensively use neuropeptides. Here we report cloning from the freshwater cnidarian Hydra of a novel ion channel (Hydra sodium channel, HyNaC) that is directly gated by the neuropeptides Hydra-RFamides I and II and is related to FaNaC. The cells expressing HyNaC localize to the base of the tentacles, adjacent to the neurons producing the Hydra-RFamides, suggesting that the peptides are the natural ligands for this channel. Our results suggest that neuropeptides were already used for fast transmission in ancient nervous systems.